Total laparoscopic-assisted radical gastrectomy (D2+) with jejunal Roux-en-Y reconstruction - Zang, Weidong; Liu, Wenju; Wei, Cheng; Liu, Shifu; Zhao, Guodong (Chinese Journal of Cancer Research; Vol 25, No 4 (August 24, 2013): Chinese Journal of Cancer Research, 2013)
Total laparoscopic-assisted radical gastrectomy and the jejunal Roux-en-Y anastomosis were performed to treat cancer of the upper gastric body and fundic region. In the case of open anastomosis during total laparoscopic-assisted radical gastrectomy, an incision of 6-8 cm would be required due to the need for placing the stapler anvil. If using the Roux-en-Y procedure, however, the incision could be reduced to as small as 4-5 cm without increasing the length of operation and intraoperative bleeding that favors postoperative recovery.